Strengthening Governance of Local Water and Sanitation Utilities for Improved Service Delivery - Ndaw, Mouhamed Fadel (World Bank, Washington, DC, 2017)
This report provides an overview of capacity-building activities undertaken after 18 months of implementation of the PforR and draws the lessons learned that can be replicated by other similar programs in the region and beyond. All activities in this report have been planned and implemented by the government and WSP provided funding and technical support. The remainder of this report is structured as follows: section two provides an overview of the design of capacity-building support. Section three presents the methodology for the implementation of the capacity-building activities and the challenges faced during implementation. Section four presents the case studies which provide detailed information on capacity-building support for procurement, citizen engagement, and M&E. Section five draws lessons learned from the abovementioned case studies. Appendix B includes the main outputs and materials produced as part of the capacity-building support.